2018
DOI: 10.3390/s18103239
|View full text |Cite
|
Sign up to set email alerts
|

Unobtrusive Photoplethysmographic Monitoring Under the Foot Sole while in a Standing Posture

Abstract: Photoplethysmography (PPG) of the foot sole could provide additional health-related information compared with traditional PPG of the finger or wrist. Previously, foot PPG required the procedural binding of a light-emitting diode (LED)-photodetector (PD) pair. We achieved PPG of the foot sole without binding any sensors to the foot while the participant stood in a natural standing position on the testing device. Foot PPG was performed using multiple LED-PD pairs to overcome motion artefacts caused by stabilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…(1) Image processing (IP)-based [49][50][51][52][53][54]; (2) floor sensors (FS)-based [55][56][57][58]; and (3) wearable sensors (WS)-based [12][13][14][15][16][17][18][19][20][21] which are worn and carried by the user [59]. The IP-based system captures image data of the subject's gait through one or multiple optical sensors and extracts gait information through digital image processing [49][50][51][52][53][54].…”
Section: Gait and Activity Monitoringmentioning
confidence: 99%
See 3 more Smart Citations
“…(1) Image processing (IP)-based [49][50][51][52][53][54]; (2) floor sensors (FS)-based [55][56][57][58]; and (3) wearable sensors (WS)-based [12][13][14][15][16][17][18][19][20][21] which are worn and carried by the user [59]. The IP-based system captures image data of the subject's gait through one or multiple optical sensors and extracts gait information through digital image processing [49][50][51][52][53][54].…”
Section: Gait and Activity Monitoringmentioning
confidence: 99%
“…In order to overcome these limitations, researchers have been focusing on wearable sensors (WS)-based gait and activity monitoring systems [12][13][14][15][16][17][18][19][20][21]. Modern miniature and lightweight wearable sensors with wireless connectivity have made it possible to develop user-friendly gait analysis systems and to obtain real-time gait data without hindering the user's regular day-to-day activities.…”
Section: Gait and Activity Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…Wu, W et al [7] used a broadband light source and color filters to determine pulse rate and arterial blood oxygen saturation. Hong, S et al [8] selected the sole of the foot as the sampling site rather than the finger or the wrist and optimized the sensor position using LED-PD pairs. Hernando, A et al [9] showed that a forehead Pulse Amplitude Variability (PAV) signal has a non-respiratory component that was unable to estimate respiratory rate (RR).…”
Section: Introductionmentioning
confidence: 99%